Composite solid electrolyte and preparation method and application thereof

By mixing the oxide solid electrolyte with the sulfide solid electrolyte in a specific proportion and adding specific additives to form a composite solid electrolyte, the air stability and elastic modulus of mixed solid electrolyte in lithium-ion batteries is solved. Problem, significantly improves the air stability and circulation performance of the battery, extends the battery's service life and improves safety.

CN119297380AInactive Publication Date: 2025-01-10SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411412799.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In actual applications, existing mixed solid electrolytes have problems such as poor air stability and low elastic modulus, which affect the safety and mechanical properties of lithium-ion batteries.

Method used

By mixing the oxide solid electrolyte and the sulfide solid electrolyte in a specific particle size ratio, and adding additives such as polyvinyl alcohol, polyvinylidene fluoride, silica or alumina, to form a composite solid electrolyte and performing ball milling to improve the material Dense and mechanical strength.

Benefits of technology

It significantly improves the air stability and circulation performance of the entire sulfide battery, improves the ion conductivity, mechanical strength and elastic modulus of the composite solid electrolyte, extends the service life of the battery and improves safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297380A_ABST
    Figure CN119297380A_ABST
Patent Text Reader

Abstract

The invention discloses a composite solid electrolyte and a preparation method and application thereof. The composite solid electrolyte comprises an oxide solid electrolyte, a sulfide solid electrolyte and an additive, wherein the particle size a of the oxide solid electrolyte and the particle size b of the sulfide solid electrolyte meet the following condition: b = C 10%-50% > a, and a is more than thousands of 0; the additive comprises any one or a combination of more of polyvinyl alcohol, polyvinylidene fluoride, silicon dioxide and aluminum oxide. The composite solid electrolyte provided by the invention has excellent ionic conductivity, mechanical strength and elastic modulus; meanwhile, the sulfide total battery prepared from the composite solid electrolyte has excellent air stability and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid electrolytes, and in particular relates to a composite solid electrolyte and a preparation method and application thereof. Background Art

[0002] As the global demand for clean energy grows, lithium-ion batteries are increasingly used as an efficient and environmentally friendly way of energy storage. However, the performance of lithium-ion batteries is restricted by their electrolyte materials. Although traditional liquid electrolytes have high conductivity, their flammability and volatility pose a safety hazard to the battery. Solid electrolytes, on the other hand, have good thermal and chemical stability and can effectively avoid these problems. Among them, oxide solid electrolytes such as LATP and LLZO, and sulfide solid electrolytes such as LPSCl, are the two types of solid electrolytes that are currently being studied more. However, existing hybrid solid electrolytes still have some problems in practical applications. First, due to the reaction of sulfide solid electrolytes with moisture and oxygen in the air, the air stability of the battery is poor. Secondly, the elastic modulus of the hybrid solid electrolyte is low, which affects the mechanical properties and energy density of the battery. Therefore, how to improve the air stability and cycle performance of sulfide full batteries, and how to improve the elastic modulus of hybrid solid electrolytes, are issues that need to be urgently addressed in this field. Summary of the invention

[0003] The main purpose of the present invention is to provide a composite solid electrolyte and a preparation method and application thereof, so as to overcome the deficiencies of the prior art.

[0004] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0005] The embodiment of the present invention provides a composite solid electrolyte, which includes: an oxide solid electrolyte, a sulfide solid electrolyte and an additive;

[0006] Among them, the particle size a of the oxide solid electrolyte and the particle size b of the sulfide solid electrolyte satisfy: b=(10%~50%)a, and a is greater than 0; the additive includes any one or more combinations of polyvinyl alcohol, polyvinylidene fluoride, silicon dioxide, and aluminum oxide.

[0007] The present invention also provides a method for preparing the composite solid electrolyte, which comprises:

[0008] The oxide solid electrolyte, the sulfide solid electrolyte and the additive are mixed and ball-milled to obtain a composite solid electrolyte.

[0009] The embodiments of the present invention also provide the use of the aforementioned composite solid electrolyte in preparing a solid electrolyte for a battery or a sulfide full battery.

[0010] An embodiment of the present invention further provides a solid electrolyte for a battery, which includes the aforementioned composite sulfide solid electrolyte.

[0011] An embodiment of the present invention further provides a sulfide full battery, which includes: a positive electrode, a negative electrode and a solid electrolyte; wherein the solid electrolyte includes the aforementioned composite solid electrolyte or a solid electrolyte for a battery.

[0012] Compared with the prior art, the present invention has the following beneficial effects:

[0013] (1) The composite solid electrolyte of the present invention has excellent ionic conductivity, mechanical strength and elastic modulus;

[0014] (2) The sulfide full battery prepared using the composite solid electrolyte in the present invention has excellent air stability and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 is a SEM image of the composite solid electrolyte in Example 1 of the present invention;

[0017] Figure 2 is the ionic conductivity diagram of the composite solid electrolyte in Example 1 of the present invention;

[0018] Figure 3 It is a diagram of the Li+ conduction mechanism of an oxide solid electrolyte and a composite solid electrolyte in a typical implementation scheme of the present invention. DETAILED DESCRIPTION

[0019] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution mainly involves mixing oxide solid electrolytes, sulfide solid electrolytes and additives to form a composite solid electrolyte. This mixing method can effectively improve the air stability of the sulfide full battery and improve its cycle performance.

[0020] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Specifically, as one aspect of the technical solution of the present invention, a composite solid electrolyte includes: an oxide solid electrolyte, a sulfide solid electrolyte and an additive;

[0022] Among them, the particle size a of the oxide solid electrolyte and the particle size b of the sulfide solid electrolyte satisfy: b=(10%~50%)a, and a is greater than 0; the additive includes any one or more combinations of polyvinyl alcohol, polyvinylidene fluoride, silicon dioxide, and aluminum oxide, and is not limited thereto.

[0023] In some preferred embodiments, the particle size a of the oxide solid electrolyte is 1 to 10 μm.

[0024] In some preferred embodiments, the particle size b of the sulfide solid electrolyte is 0.1 to 5 μm.

[0025] In some preferred embodiments, the particle size of the additive is 1 nm to 100 nm.

[0026] The Li+ conduction mechanism of the oxide solid electrolyte and composite solid electrolyte in the present invention is shown in FIG. Figure 3 As shown; in the present invention, by limiting the size of the oxide solid electrolyte and the sulfide solid electrolyte and introducing additives, the composite solid electrolyte forms a special distribution in the microstructure: smaller sulfide particles are evenly distributed between larger oxide particles. When the sulfide particle size is in the range of 10%-50% of the oxide particles, the best filling effect can be achieved, the porosity can be reduced, and the density and mechanical strength of the material can be improved. The additive promotes the close bonding between the two electrolyte particles, optimizes the ion conduction path and the mechanical strength of the material; at the same time, the larger oxide particles provide mechanical support for the overall structure, the smaller sulfide particles fill the gaps between the oxide particles, and the additive enhances the adhesion and stability of the overall material, thereby significantly improving the elastic modulus of the composite solid electrolyte.

[0027] In some preferred embodiments, the mass ratio of the oxide solid electrolyte to the sulfide solid electrolyte is 10:1 to 2:1.

[0028] In some preferred embodiments, the content of the additive in the composite solid electrolyte is 0.1 wt% to 10 wt%.

[0029] In some preferred embodiments, the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3(LATP) and / or Li7La3Zr2O 12 (LLZO), but not limited thereto.

[0030] In some preferred embodiments, the sulfide solid electrolyte (LPSCl) includes Li 5.5 PS 4.5 Cl 1.5 and / or Li6PS5Cl, but are not limited thereto.

[0031] In the present invention, the sulfide solid electrolyte particles are distributed between the oxide solid electrolyte particles, forming a protective effect of the oxide on the sulfide. The additive further improves the density of the material and can effectively prevent the sulfide from contacting with moisture and oxygen in the air, thereby improving the air stability of the mixed electrolyte; at the same time, the special structure of the composite solid electrolyte and the introduction of the additive help to reduce the volume change of the material during the charge and discharge process of the battery, thereby improving the cycle performance of the battery.

[0032] Another aspect of the embodiments of the present invention further provides a method for preparing the aforementioned composite solid electrolyte, which comprises:

[0033] The oxide solid electrolyte, the sulfide solid electrolyte and the additive are mixed and ball-milled to obtain a composite solid electrolyte.

[0034] In some more specific embodiments, the method for preparing the composite solid electrolyte comprises the following steps:

[0035] Prepare oxide solid electrolyte LATP or LLZO and sulfide solid electrolyte LPSCl and additives, mix the three in a certain proportion, put these substances into a ball mill, and ball mill at a speed of 300 rpm for 2-4 hours to obtain a uniformly mixed composite solid electrolyte.

[0036] The oxide solid electrolyte, sulfide solid electrolyte and additives need to meet the following requirements:

[0037] (1) The particle size of the oxide solid electrolyte is controlled between 1 μm and 10 μm.

[0038] (2) The particle size of the sulfide solid electrolyte is controlled between 0.1 μm and 5 μm.

[0039] (3) The particle size ratio of the oxide solid electrolyte and the sulfide solid electrolyte satisfies the relationship of "sulfide solid electrolyte size = 10% - 50% oxide solid electrolyte size".

[0040] (4) The additive is polyvinyl alcohol (PVA), polyvinylidene fluoride (PVDF) or silicon dioxide (SiO2) nanoparticles or aluminum oxide (Al2O3) nanoparticles. The particle size of the additive should be controlled between 1 nm and 100 nm, and its weight percentage is 0.1% to 10% of the overall mixture.

[0041] The present invention mixes an oxide solid electrolyte LATP or LLZO, a sulfide solid electrolyte LPSCl and an additive to form a composite solid electrolyte. This mixing method can effectively improve the air stability of the sulfide full battery and improve its cycle performance. In the preparation process of the composite solid electrolyte, the elastic modulus of the composite solid electrolyte can be further improved by adjusting the proportion of raw materials and reaction conditions, which can not only improve the mechanical strength of the battery, but also improve the electrochemical performance of the battery. In the use of the battery, the air stability and cycle performance of the battery can be further improved through reasonable charge and discharge management and temperature control, which can not only extend the service life of the battery, but also improve the safety of the battery.

[0042] Another aspect of the embodiments of the present invention further provides the use of the aforementioned composite solid electrolyte in preparing a solid electrolyte for a battery or a sulfide full battery.

[0043] Another aspect of an embodiment of the present invention further provides a solid electrolyte for a battery, which includes the aforementioned composite sulfide solid electrolyte.

[0044] Another aspect of an embodiment of the present invention further provides a sulfide full battery, which includes: a positive electrode, a negative electrode and a solid electrolyte; wherein the solid electrolyte includes the aforementioned composite solid electrolyte or a solid electrolyte for a battery.

[0045] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments. This embodiment is implemented on the premise of the technical solution of the invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0046] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.

[0047] Example 1

[0048] Step 1: Prepare the oxide solid electrolyte LATP and the sulfide solid electrolyte LPSCl (Li 5.5 PS 4.5 Cl 1.5) and silicon dioxide nanoparticles, the three are mixed in a certain ratio of 8:1.5:0.5, these materials are put into a ball mill, and ball milled at a speed of 300rpm for 2-4 hours to obtain a composite solid electrolyte. The SEM image of the composite solid electrolyte is shown in Figure 1 As shown in the figure, the ionic conductivity of the composite solid electrolyte is Figure 2 shown.

[0049] The oxide solid electrolyte LATP, the sulfide solid electrolyte LPSCl and the silicon dioxide nanoparticles need to meet the following requirements:

[0050] (1) The particle size of the oxide solid electrolyte LATP is 10 μm and the mass is 0.2 g;

[0051] (2) The particle size of the sulfide solid electrolyte LPSCl is 3 μm and the mass is 0.1 g;

[0052] (3) The particle size ratio of the oxide solid electrolyte LATP and the sulfide solid electrolyte LPSCl satisfies: the size of the sulfide solid electrolyte LPSCl = 30% of the oxide solid electrolyte LATP;

[0053] (4) The particle size of the silicon dioxide nanoparticles is 50 nm; and the weight percentage thereof is 0.5% of the mass of the mixture of oxides and sulfides;

[0054] Step 2: Place the composite solid electrolyte into a tablet press, press it under a pressure of 2t, and take it out after 10 minutes.

[0055] Step 3: Mix the composite solid electrolyte and the positive electrode materials LiCoO2, LFP, and NCM in a mass ratio of 1:1 and add them to the electrolyte sheet for further compaction.

[0056] Step 4: Place the negative electrode lithium into the mold to obtain a sulfide full battery. During this process, the battery's charge cutoff voltage is controlled to be 4.2V and the discharge cutoff voltage is controlled to be 2.75V.

[0057] Step 5: The prepared sulfide full battery was left at room temperature for 24 hours, and then the charge and discharge test was performed. During the test, the charge and discharge current was controlled to be 0.5C, and the charge and discharge voltage range was 2.75V-4.2V.

[0058] Example 2

[0059] The method is the same as in Example 1, except that:

[0060] (1) The particle size of the oxide solid electrolyte LATP is 1 μm;

[0061] (2) Sulfide solid electrolyte LPSCl (Li 5.5 PS4.5 Cl 1.5 ) has a particle size of 0.1 μm;

[0062] (3) Oxide solid electrolyte LATP and sulfide solid electrolyte LPSCl (Li 5.5 PS 4.5 Cl 1.5 ) has a particle size ratio that satisfies: sulfide solid electrolyte LPSCl (Li 5.5 PS 4.5 Cl 1.5 ) size = 10% oxide solid electrolyte LATP;

[0063] (4) The particle size of the silicon dioxide nanoparticles is 1 nm; and the weight percentage thereof is 0.1% of the entire mixture;

[0064] (5) Oxide solid electrolyte LATP and sulfide solid electrolyte LPSCl (Li 5.5 PS 4.5 Cl 1.5 ) is in a mass ratio of 10:1.

[0065] Example 3

[0066] The method is the same as in Example 1, except that the additive is polyvinyl alcohol;

[0067] (1) The particle size of the oxide solid electrolyte LATP is 10 μm;

[0068] (2) The particle size of the sulfide solid electrolyte LPSCl (Li6PS5Cl) is 5 μm;

[0069] (3) The particle size ratio of the oxide solid electrolyte LATP and the sulfide solid electrolyte LPSCl (Li6PS5Cl) satisfies: the size of the sulfide solid electrolyte LPSCl (Li6PS5Cl) = 50% of the oxide solid electrolyte LATP;

[0070] (4) The particle size of polyvinyl alcohol is 100 nm; and its weight percentage is 10% of the whole mixture;

[0071] (5) The mass ratio of the oxide solid electrolyte LATP to the sulfide solid electrolyte LPSCl (Li6PS5Cl) is 2:1.

[0072] Example 4

[0073] The method is the same as in Example 1, except that the additive is aluminum oxide;

[0074] (1) The particle size of the oxide solid electrolyte LLZO is 5 μm;

[0075] (2) The particle size of the sulfide solid electrolyte LPSCl (Li6PS5Cl) is 1 μm;

[0076] (3) The particle size ratio of the oxide solid electrolyte LLZO and the sulfide solid electrolyte LPSCl (Li6PS5Cl) satisfies: the size of the sulfide solid electrolyte LPSCl (Li6PS5Cl) = 20% of the oxide solid electrolyte LLZO;

[0077] (4) The particle size of the aluminum oxide nanoparticles is 50 nm; and the weight percentage thereof is 5% of the entire mixture;

[0078] (5) The mass ratio of the oxide solid electrolyte LATP to the sulfide solid electrolyte LPSCl (Li6PS5Cl) is 5:1.

[0079] Comparative Example 1

[0080] The method is the same as in Example 1, except that no silicon dioxide nanoparticles are added.

[0081] Comparative Example 2

[0082] The method is the same as that of Example 1, except that the particle size of the sulfide solid electrolyte LPSCl is 10 μm.

[0083] Comparative Example 3

[0084] The method is the same as that of Example 1, except that the particle size of the sulfide solid electrolyte LPSCl is 0.1 μm.

[0085] Comparative Example 4

[0086] The method is the same as that of Example 1, except that the particle size of the sulfide solid electrolyte LPSCl is 0.01 μm.

[0087] Comparative Example 5

[0088] The method is the same as that of Example 1, except that the particle size of the oxide solid electrolyte LPSCl is 15 μm.

[0089] Comparative Example 6

[0090] The method is the same as that of Example 1, except that the particle size of the oxide solid electrolyte LPSCl is 20 μm.

[0091] Comparative Example 7

[0092] The method is the same as that of Example 1, except that the particle size of the oxide solid electrolyte LPSCl is 0.5 μm.

[0093] Comparative Example 8

[0094] The method is the same as that of Example 1, except that the particle size of the oxide solid electrolyte LPSCl is 3 μm.

[0095] Comparative Example 9

[0096] The method is the same as that of Example 1, except that the content of silicon dioxide nanoparticles is 0.05%.

[0097] Comparative Example 10

[0098] The method is the same as that of Example 1, except that the content of silicon dioxide nanoparticles is 15%.

[0099] Comparative Example 11

[0100] The method is the same as that of Example 1, except that silicon dioxide particles with a particle size of 1 μm are used instead of nanoparticles.

[0101] The ionic conductivity, elastic modulus and battery performance of the solid electrolytes in the above Examples 1-4 and Comparative Examples 1-10 are shown in Table 1.

[0102] Table 1

[0103]

[0104] The technical solution provided in the present invention can be widely used in application fields such as battery manufacturing, solid electrolyte material research and development, chemical engineering and materials science. First of all, this technical solution improves the air stability and cycle performance of the sulfide full battery by mixing oxide solid electrolytes and sulfide solid electrolytes. For the battery manufacturing industry, this undoubtedly greatly improves the safety and service life of the battery, and meets the market demand for high-safety, long-cycle life batteries. Secondly, this technical solution also improves the elastic modulus of the mixed solid electrolyte, which provides a new solid electrolyte design idea for the field of solid electrolyte material research and development, and helps to develop solid electrolyte materials with better performance. Finally, this technical solution involves knowledge in the fields of chemical engineering and materials science, and also plays an important role in promoting scientific research and industrial development in these two fields.

[0105] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0106] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.

Claims

1. A composite solid electrolyte, characterized in that: include: An oxide solid electrolyte, a sulfide solid electrolyte and an additive; wherein the particle size a of the oxide solid electrolyte and the particle size b of the sulfide solid electrolyte satisfy: b = (10% to 50%) a, and a is greater than 0; the additive comprises any one or more combinations of polyvinyl alcohol, polyvinylidene fluoride, silicon dioxide and aluminum oxide.

2. The composite solid electrolyte according to claim 1, characterized in that: The particle size a of the oxide solid electrolyte is 1 to 10 μm; And / or, the particle size b of the sulfide solid electrolyte is 0.1 to 5 μm; And / or, the particle size of the additive is 1 nm to 100 nm.

3. The composite solid electrolyte according to claim 1, characterized in that: The mass c of the oxide solid electrolyte and the mass d of the sulfide solid electrolyte satisfy: d=(10% to 50%)c.

4. The composite solid electrolyte according to claim 1, characterized in that: The content of the additive in the composite solid electrolyte is 0.1wt% to 10wt%.

5. The composite solid electrolyte according to claim 1, characterized in that: The oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3 and / or Li7La3Zr2O 12 .

6. The composite solid electrolyte according to claim 1, characterized in that: The sulfide solid electrolyte includes Li 5.5 PS 4.5 Cl 1.5 and / or Li6PS5Cl.

7. The method for preparing a composite solid electrolyte according to any one of claims 1 to 6, characterized in that: include: The oxide solid electrolyte, the sulfide solid electrolyte and the additive are mixed and ball-milled to obtain a composite solid electrolyte.

8. Use of the composite solid electrolyte according to any one of claims 1 to 6 in preparing a solid electrolyte for a battery or a sulfide full battery.

9. A solid electrolyte for a battery, characterized in that: The invention comprises the composite sulfide solid electrolyte according to any one of claims 1 to 6.

10. A sulfide full battery, characterized in that: include: A positive electrode, a negative electrode and a solid electrolyte; wherein the solid electrolyte comprises the composite solid electrolyte according to any one of claims 1 to 6 or the solid electrolyte for a battery according to claim 9.

Citation Information

Patent Citations

  • Composite solid electrolyte

    CN106848389A

  • Composite solid electrolyte and preparation method thereof

    CN109509910A

  • Solid electrolyte, preparation method thereof, and all-solid-state battery

    CN113937346A

  • Composite solid-state electrolyte, composite solid-state electrolyte membrane and preparation method thereof, and solid-state battery

    CN114649567A

  • Method for preparing sulfide / oxide solid electrolyte with melon pulp structure by mechanical method

    CN117174991A